Penggambaran Kejahatan di Area Urban dalam Docuseries “Asumsi Distrik” - Hanifah Nur Fadhila (Jurnal Kriminologi Indonesia, 2020)
In a time where mass-mediated culture is prominently consumed in our society, the right portrayals of crime becomes primary. This goes without saying that media in popular culture often featured highly visible crimes to be portrayed as exaggerating and exhilarating phenomenon. Thus, this paper is set to acknowledge the ever-growing portrayals of the dynamic of crime in urban area presented in docuseries “Asumsi Distrik”. Using Jeff Ferrell’s cultural criminology framework, this study also viewed the depiction of the inhabitants in urban area to be categorized as “crime as culture”. Moreover, Asumsi Distrik hereby posed as a medium to bring the visibility of crime of the powerful that often overlooked by the media.